Analisis Lughawi dalam Tafsir Al-Munir Karya Wahbah Zuhaili (W. 2015 M) - Eka Prasetiawati Eka; Dian Risky Amalia; Muhammad Irsad (AL QUDS : Jurnal Studi Alquran dan Hadis, 2025)
This article examines the grammatical (linguistic) approach in al-Munīr’s interpretation of Qur’anic verses related to religious moderation. However, previous studies generally discuss religious moderation thematically without examining the linguistic strategies used by Wahbah Zuḥaylī in Tafsir al-Munīr. How is nahwu analysis applied in the interpretation of verses on religious moderation and its linguistic implications in constructing a discourse of moderation? This study shows that the lughawī approach not only functions as a tool for text analysis but also as a mechanism for creating the meaning of moderation in contemporary tafsir. The primary focus of this study is how linguistic aspects, such as i’rab, mufradat meaning, balaghah, and syntactic and morphological structures, are used by Zuhaili to form a moderate narrative in a religious and national context. This study uses a qualitative method based on a literature review with a descriptive-analytical approach. Primary data is sourced from Tafsir al-Munir, while secondary data is obtained from other Arabic exegesis and linguistic works. The linguistic approach in this study focuses on nahwu analysis through i’rab and mufradat in Tafsir al-Munīr. The verses were selected thematically, in line with the Indonesian Ministry of Religious Affairs’ indicators of Religious Moderation. The results show that Zuhaili consistently applies a linguistic interpretation pattern through etymological, semantic, and syntactic approaches, which strengthen the understanding of verses on defending the country, tolerance, justice, leadership, and unity. The emphasis on the accuracy of word meaning and sentence structure in these verses clarifies messages of moderation, such as love for the homeland, anti-extremism, and respect for diversity